CONTROL SYSTEM FOR INTERNET OF THINGS (IOT) BASED AIR CONDITIONER (AC) SYSTEM - Septhian Siahaan, Perystito
Energy saving is one solution to prevent energy scarcity. In this study, savings were made on the Air Conditioner (AC) system. Energy saving is done by regulating the state of the compressor on the AC so that the burden of energy consumption can be reduced. Adjustment of the device to save energy can be done by controlling and monitoring the device. Control and monitoring systems can be implemented using Internet of Things (IoT) technology. IoT is the concept of communicating one device to another over a network. The IoT technology system consists of a transducer, visualization device and cloud. In this study, transducer devices are temperature and humidity sensors, power measuring modules, and relay modules. Visualization tools are devices from the user. Temperature and humidity sensors and power measuring modules will measure the associated physical quantities then send the data to the cloud for processing and then followed up by controlling the AC system via a relay. Control the relay resulting in changes in temperature in the room. Thus, implementing a control system on the relay can regulate the use of energy by the AC to achieve a reduction in energy consumption and make changes in the room temperature to achieve the desired temperature.